1996
DOI: 10.1074/jbc.271.39.24129
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Fibrin Intermediate Arising from Cleavage of One Fibrinopeptide A from Fibrinogen

Abstract: The thrombin-catalyzed cleavage of N-terminal fibrinopeptide A (FPA) from the two Aalpha-chains of fibrinogen exposes aggregation sites with the critical sequence GPR located just behind FPA. It is well known that exposure of both GPR sites transforms fibrinogen into self-aggregating, fully coagulable alpha-fibrin monomers, but the fibrin precursor with one site exposed and one FPA intact has eluded description. The formation of this "alpha-profibrin" in the course of thrombin reactions and its distribution am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…[50][51][52] GPRphoresis uses electrophoresis to cause the countermigration of Gly-pro-arg-pro amide (GPRP-NH 2 ; Bachem Biosciences, King of Prussia, PA) in GPRP-NH 2 -impregnated gels to separate GPRP-NH 2 -insoluble fibrin monomers lacking both FPAs (␣-fibrin) from a fibrin intermediate termed ␣-profibrin lacking only one FPA, and it is soluble in buffer solutions lacking GPRP-NH 2 . After electrophoresis, the band containing ␣-profibrin comigrates with fibrinogen and is distinguished from it by immunoprobing the gel with an anti-fibrin ␣17-23 antibody (Roche Diagnostics, Basel, Switzerland) that reacts with ␣-fibrin or ␣-profibin but not with fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
“…[50][51][52] GPRphoresis uses electrophoresis to cause the countermigration of Gly-pro-arg-pro amide (GPRP-NH 2 ; Bachem Biosciences, King of Prussia, PA) in GPRP-NH 2 -impregnated gels to separate GPRP-NH 2 -insoluble fibrin monomers lacking both FPAs (␣-fibrin) from a fibrin intermediate termed ␣-profibrin lacking only one FPA, and it is soluble in buffer solutions lacking GPRP-NH 2 . After electrophoresis, the band containing ␣-profibrin comigrates with fibrinogen and is distinguished from it by immunoprobing the gel with an anti-fibrin ␣17-23 antibody (Roche Diagnostics, Basel, Switzerland) that reacts with ␣-fibrin or ␣-profibin but not with fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
“…Fibrin-free fibrinogen (18) was provided by Dr. J. Shainoff (Cleveland Clinic Foundation, Cleveland, OH). Human fibronectin purified according to the method of Vuento and Vaheri (19) was a gift from Dr. T. Ugarova (Cleveland Clinic Foundation, Cleveland, OH).…”
Section: Methodsmentioning
confidence: 99%
“…Using electrophoretic conditions that allow the separation of fibrin from fibrinogen monomer and subsequent visualization using Coomassie violet R-250 (18), the isolated material was estimated to comprise greater than 95% fibrinogen. Preparations of Fg were also analyzed for the presence of free fibrinopeptides A and B by elution on a Sep-Pak C 18 high pressure liquid chromatography column using standard preparations of each of the fibrinopeptides (Sigma). At protein concentrations of at least 50-fold greater than those used in these experiments, amounts of fibrinopeptides A and B were below detectable levels.…”
Section: Methodsmentioning
confidence: 99%
“…The release of a second set of fibrinopeptides, FPB, trails the release of FPA and enables further coupling of interactions within the protofibrils, which in turn enhances their lateral aggregation (9,10). Our preceding study (5) shows that the maximal level of ␣-profibrin achieved in the course of fibrin formation was half of what would be expected if the rate constants for the release of the first and second FPA were equal. The low level of ␣-profibrin suggested that either 1) there was a partial coupling of the release of the second FPA with the first or 2) ␣-profibrin was a better substrate enabling thrombin to release the remaining FPA at a rate appearing three times faster than release of the first.…”
mentioning
confidence: 88%
“…The release of the first FPA produces an intermediate, ␣-profibrin, that aggregates so weakly that it had been difficult to distinguish from fibrinogen until recently (5). The release of the second FPA enables cooperative interactions of the resulting ␣-fibrin molecules with other fibrin(ogen) molecules forming either soluble double-stranded protofibrils or laterally coalesced insoluble fibrin strands.…”
mentioning
confidence: 99%